The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.33182/ks.v2i2.399
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in Kurmanji: A preliminary classification of dialects

Abstract: Historical linguistic sources of Kurdish date back just a few hundred years, thus it is not possiInvestigation of the regional variation in Kurmanji, especially its varieties spoken in Turkey, has been almost entirely neglected in the existing literature on Kurdish. In addition to earlier isolated examinations of Kurmanji dialects (cf. MacKenzie, 1961; Ritter, 1971, 1976; Blau, 1975; Jastrow, 1977), native-speaker researchers have recently provided a substantial amount of dialect material across the Kurmanji-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…Based on Öpengin and Haig (2014) While it is conceivable that further research on the dialects of Kurmanji will reveal other factors such as religious affinity, i.e. whether the dialect community is of the Alevi or Sunni sect, to be also crucial in defining variation across dialects, our findings nevertheless provide evidence to the act that geographical factors indeed do play a significant role in determining the properties of the individual dialects (Özsoy and Türkyılmaz 2006:300).…”
Section: Languagementioning
confidence: 54%
“…Based on Öpengin and Haig (2014) While it is conceivable that further research on the dialects of Kurmanji will reveal other factors such as religious affinity, i.e. whether the dialect community is of the Alevi or Sunni sect, to be also crucial in defining variation across dialects, our findings nevertheless provide evidence to the act that geographical factors indeed do play a significant role in determining the properties of the individual dialects (Özsoy and Türkyılmaz 2006:300).…”
Section: Languagementioning
confidence: 54%
“… See L'alphabet Kurde Adapte Aux Caracteres Latins by Akın (2006) for detailed information (socio-political, linguistic and historical developments) about the use of Latin characters for Kurdish.3 Being the first professional research in Kurdish dialectology, Öpengin and Haig's study on dialect regions of Kurmanji spoken in Turkey is invaluable. The results of the current study would be more meaningful if they are interpreted and compared with other Kurmanji dialects mentioned inÖpengin and Haig (2014). Also, the morphosyntactic properties of Muş Kurmanji are investigated in comparison to the Standard Kurmanji in an earlier study so seeGündoğdu (2011) for a detailed analysis.…”
mentioning
confidence: 88%
“…Therefore, eight vowels in orthography correspond to ten vowels in the spoken form of Muş Kurmanji. The vowels in Muş Kurmanji are provided in the table below (the vowels corresponding to more than one sound are put together): As it is mentioned in earlier studies such as Blau (1989), Özsoy and Türkyılmaz (2006), Thackston (2006), Öpengin and Haig (2014), the stops and affricates in Kurmanji exhibit a three-way contrast between aspirated and unaspirated voiceless stop and a voiced stop, e.g., aspirated voiceless velar stop /k h /, unaspirated voiceless velar stop /k/ and voiced velar stop /g/. It has been observed that aspiration also makes a distinction in Muş Kurmanji.…”
Section: Vowels In Kurmanji Kurdishmentioning
confidence: 99%
“…I will use these terms only when necessary otherwise I will use the terms Bohtan and Maraş since it was these that were used by participants during my ethnographic fieldwork. MRKr shows highly divergent features -lexically and phonologically -from BHKr, and it is the most stigmatised [variety] among all the Kurmanji varieties (Öpengin and Haig 2014). This stigma is assigned in all levels of Kurdish society because MRKr is stereotyped as a mixture of Turkish and Kurdish and hence identified as a "contaminated" variety.…”
Section: Kurmanji and Variationmentioning
confidence: 99%
“…In the actual study I asked the respondents to write the name of a city where they guessed the speaker was from. I categorised these regions on the basis of Öpengin and Haig (2014). Drawing on the perceptions of the listeners, BHKr corresponds to cities such as Mardin, Batman, Sirnak and Urfa.…”
Section: Figurementioning
confidence: 99%